Effect of Co-Electrodeposited Cu-Zn-Sn Precursor Compositions on Sulfurized CZTS Thin Films for Solar Cell. (10th February 2015) - Khalil, Md Ibrahim; Bernasconi, Roberto; Ieffa, Simona; Lucotti, Andrea; Le Donne, Alessia; Binetti, Simona; Magagnin, Luca
Abstract : Electrodeposition followed by sulfurization could be a favourable process for the fabrication of the CZTS thin film solar cells. Here we attempt to fabricate CZTS thin films from co-electrodeposited precursors of Cu-Zn-Sn with various compositions from Cu-poor, Zn-rich to Cu-rich, Zn-poor. Different characterization methods like XRD, SEM (EDS), and Raman spectroscopy have been employed to investigate the structure, morphology, and composition as well as the precursor compositional effect on the final sulfurized films. From the results, by electrodeposition it is possible to form a good crystalline form of Kesterite CZTS with the help of precise control of precursor compositions (Cu-poor, Zn-rich) in order to overcome the volatility effect of Zn and Sn during annealing at high temperature.